Smoking cessation programmes for women living in disadvantaged communities, We Can Quit 2 : A systematic review protocol - Darker, Catherine; Mockler, David; O'Connell, Nicola; Hayes, Catherine (My University, 2019)
Tobacco use is the leading cause of preventable death in Ireland with almost 6,000 smokers dying each year from smoking-related diseases. Amongst younger Irish women, smoking rates are considerably higher in those from socially disadvantaged areas compared to women from affluent areas. Women from poorer areas also experience higher rates of lung cancer. To our knowledge, there are no peer reviewed published systematic reviews on the effectiveness of interventions tailored to reduce smoking rates in women from disadvantaged areas. This systematic review protocol will aim to examine the effectiveness of such interventions and to describe trial processes such as recruitment, follow-up and dropout prevention strategies, as well as barriers and enablers of successful implementation. A systematic review will be conducted of peer-reviewed randomised controlled trials and associated process evaluations of smoking cessation interventions designed for women living in socially disadvantaged areas. If the search returns, less than five studies are review criteria will expand to include quasi-experimental studies. A number of databases of scholarly literature will be searched from inception using a detailed search strategy. Two independent reviewers will screen titles, abstracts and full-text articles to identify relevant studies using a pre-defined checklist based on PICOS. In the case of disagreement, a third reviewer will be consulted. The quality of included studies will be assessed using the 'Grading of Recommendations Assessment, Development and Evaluation' (GRADE) criteria. Quantitative data will be extracted and, if comparable, will be assessed using meta-analysis. A narrative meta-synthesis of qualitative data will be conducted. This review aims to synthesise information from relevant studies on smoking cessation interventions tailored for women from socially disadvantaged areas. The evidence obtained from studies and presented in this review will help guide future research in this area. Registration: This review will be registered with International Prospective Register of Systematic Reviews (PROSPERO).
PUBLISHED
Keywords: Cluster Randomised Controlled Trial; Community-based Intervention; Feasibility study; Pilot trial; Smoking Cessation; Social and Health Inequalities; Systematic Review; Women and Smoking; Cancer; Inclusive Society